Oral rhabdomyosarcoma, a rare malignant tumor mimicking an endodontic-periodontal lesion in an adult patient: a case report - Fang-Yu Zheng; Juan-You Qiu; Kuo-Han Liao; Nan-Chin Lin (BMC, 2024)
Abstract Background According to previous research, 2.8% of lesions clinically identified as endodontic pathosis were ultimately diagnosed as non-endodontic periapical lesions via histopathology, and 3.7% of these non-endodontic periapical lesions were malignant neoplasms. Rhabdomyosarcoma, a malignant tumor most commonly observed in children, is uncommon in the oral cavity. Case presentation This is a report of a rare case of embryonal rhabdomyosarcoma in a 41-year-old female, in which the lesion was in the maxillary gingiva. The biopsy reports confirmed the diagnosis of embryonal rhabdomyosarcoma. The wide excision of the tumor, free flap reconstruction, chemotherapy, and radiotherapy were performed. Clinical, radiological, and histopathological and management aspects of the neoplasm were also discussed. Conclusions This case report aimed to create awareness that rhabdomyosarcoma is one of the differential diagnoses of periapical lesions.